Two new cases of interstitial 7q35q36.1 deletion including CNTNAP2 and KMT2C - Lucie Tosca (Wiley, 2021)
Abstract Background Terminal deletions of the long arm of chromosome 7 are well known and frequently associated with syndromic holoprosencephaly due to the involvement of the SHH (aliases HHG1, SMMCI, TPT, TPTPS, and MCOPCB5) gene region. However, interstitial deletions including CNTNAP2 (aliases Caspr2, KIAA0868, and NRXN4) and excluding the SHH region are less common. Methods We report the clinical and molecular characterization associated with pure 7q35 and 7q35q36.1 deletion in two unrelated patients as detected by oligonucleotide‐based array‐CGH analysis. Results The common clinical features were abnormal maternal serum screening during first‐trimester pregnancy, low occipitofrontal circumference at birth, hypotonia, abnormal feet, developmental delay, impaired language development, generalized seizures, hyperactive behavior, friendly personality, and cranio‐facial dysmorphism. Both deletions occurred de novo and sequencing of CNTNAP2, a candidate gene for epilepsy and autism showed absence of mutation on the contralateral allele. Conclusion Combined haploinsufficiency of GALNTL5 (alias GalNAc‐T5L), CUL1, SSPO (aliases SCO‐spondin, KIAA0543, and FLJ36112), AOC1 (alias DAO), RHEB, and especially KMT2C (alias KIAA1506 and HALR) with monoallelic disruption of CNTNAP2 may explain neurologic abnormalities, hypotonia, and exostoses. Haploinsufficiency of PRKAG2 (aliases AAKG, AAKG2, H91620p, WPWS, and CMH6) and KCNH2 (aliases Kv11.1, HERG, and erg1) genes may be responsible of long QT syndrome observed for one patient.